Pendampingan Program Cek Kesehatan Gratis untuk Deteksi Dini Faktor Risiko Penyakit di Payaraman Ogan Ilir - Muhammad Raffi Aidillah; Dinda Anindya Putri; Nikken Kinanti; Syahril Arya Winata; Della Futri Shalimah; Al Ayyubi; Rila Suntika; Yola Indah Sari; Muhammad Ramka Kandawi; Amar Makruf; Novelino Bayu; Meilina Wardhani; Ahmad Ghiffari (Lembaga Pengembangan Kinerja Dosen, 2026)
The Free Health Check Program is a preventive and promotive initiative aimed at expanding early detection of health risks in the community. This community service activity aimed to describe the implementation of community-based assistance for the Free Health Check Program in the working area of Payaraman Barat Public Health Center, identify major screening findings, and evaluate health communication quality. A participatory approach integrating interactive education, basic health screening, counselling, and community health worker involvement was applied. A total of 3,024 participants from children, adults, and older adults participated, with those aged 40–59 years comprising the largest group (33.33%). Among 2,081 participants with blood pressure data, 50.36% were classified outside the normal category. Body mass index assessment among 2,153 participants showed that most were classified as having excess body weight, overweight, or obesity. Communication evaluation showed that 52.91–59.52% of participants rated information clarity, language comprehensibility, staff friendliness, opportunity for questions, and communication media as good. Community health worker and local stakeholder involvement exceeded the program target. Community-based assistance may strengthen screening reach, health communication, and early identification of health risks, although standardized documentation and follow-up remain essential.